Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1109/access.2020.3027383
|View full text |Cite
|
Sign up to set email alerts
|

Antenna Design Using Modern Additive Manufacturing Technology: A Review

Abstract: printing technology is an area of research that has received great attention in the last decade and it is pointed out by many as the future of manufacturing. 3D printing can be described as an additive process that creates a physical object from a digital model, depositing materials layer by layer. The ability to quickly produce complex structures at a reduced cost and without wasting materials is the main reason why this additive manufacturing technique is increasingly being used instead of conventional manuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 95 publications
0
22
0
Order By: Relevance
“…A not exhaustive list could contain Massoni et al [ 17 ], where the authors have used the possibility to tune the infill of a model printed by FDM technology to realize a Substrate Integrated Slab Waveguide obtaining an enhanced bandwidth; Moscato et al [ 18 ], where the same principle and the use of a special elastic material called Ninjaflex have been used to produce an unconventional antenna; Rocco et al [ 19 ], in which the authors have described how they successfully manufactured a 3D-printed microfluidic sensor by exploiting a substrate integrated waveguide cavity; Martínez Odiaga et al [ 20 ], where a particularly lightweight circular horn antenna for police radar application has been printed with FDM; Alkaraki et al [ 21 ], in which authors reported the realization of a particular 3D-printed slot antenna operating in the Ka band. Eventually, in Helena et al [ 22 ], a very accurate review on different AM technology (FDM among the others) applied in the prototyping of antennas, is proposed.…”
Section: Fused Deposition Modelling In Electromagneticsmentioning
confidence: 99%
“…A not exhaustive list could contain Massoni et al [ 17 ], where the authors have used the possibility to tune the infill of a model printed by FDM technology to realize a Substrate Integrated Slab Waveguide obtaining an enhanced bandwidth; Moscato et al [ 18 ], where the same principle and the use of a special elastic material called Ninjaflex have been used to produce an unconventional antenna; Rocco et al [ 19 ], in which the authors have described how they successfully manufactured a 3D-printed microfluidic sensor by exploiting a substrate integrated waveguide cavity; Martínez Odiaga et al [ 20 ], where a particularly lightweight circular horn antenna for police radar application has been printed with FDM; Alkaraki et al [ 21 ], in which authors reported the realization of a particular 3D-printed slot antenna operating in the Ka band. Eventually, in Helena et al [ 22 ], a very accurate review on different AM technology (FDM among the others) applied in the prototyping of antennas, is proposed.…”
Section: Fused Deposition Modelling In Electromagneticsmentioning
confidence: 99%
“…For these reasons, in the open literature, 3D printing based on material extrusion is mainly employed to build only the dielectric structure of the antenna, falling back on alternative solutions to provide the metallisation [4–27]. Many types of antennas operating at very different frequencies and many techniques to realize the conductive parts have been adopted in these works.…”
Section: Introductionmentioning
confidence: 99%
“…The filaments are designed for their physical properties rather than their EM properties. ABS has a relative permittivity, , r f of ~2.69 and a loss tangent, , tan d of ~0.012, while PLA has an r f of ~2.7 and a tan d of ~0.008 measured at 1 MHz [1]. The dielectric properties were measured with a range of techniques over the frequency range of 2-60 GHz: ABS had an r f of ~2.45 and a tan d of ~0.005, and PLA had an r f of ~2.55 and a tan d of ~0.009 [2].…”
Section: Fused Filament Fabricationmentioning
confidence: 99%